Narrowband shielding against electromagnetic interference in LTE 4G systems using complementary frequency selective surfaces. Issue 9 (11th August 2018) - da Silva, B. S.; Campos, A. L. P. S.; Gomes Neto, A.
Abstract: This article presents the project and fabrication of an electromagnetic shielding using complementary frequency selective surfaces. The proposed structure acts as low pass filter in the bands 1.8–2.3 GHz and 2.86–3.47 GHz, with a narrowband null rejecting undesired frequencies, in this case, 4G band (2.50–2.69 GHz). The project begins by analyzing geometries very well known in the specific literature (cross‐dipole and square‐loop), separately, to determine the dimensions of these geometries efficiently. In addition, computational simulations of a new geometry are made, joining the initial geometries, to observe the behavior of the interaction between them. Therefore, the CFSS is proposed and studied to achieve the desired frequency response. By using the screen printing technique, the EMI shielding is fabricated. Finally, its frequency response is validated experimentally. A good agreement between measurement and simulation is demonstrated in this article, as well as the angular stability of the proposed structure.